Predicting the lifetime of CPVC under increasing temperature and crosshead speed (Fracture and Structural Integrity, 2023)
CPVC is an increasingly popular material for plumbing pipes and other applications that require strong and temperature-resistant material. This resin is created using a chlorination process, giving it Chlorine levels that range from 63 to 69% and thus a unique set of characteristics that make it ideal for certain applications. CPVC's combination of corrosion-resistance and low installation costs make it a great substitute for copper in environments with non-ambient conditions such as higher temperatures. This makes it an economic choice for many projects that require smaller budgets. With a variety of applications, CPVC provides a great alternative requiring strong and durable material. The aim of this paper is to characterize the mechanical characteristics of chlorinated PVC (CPVC). Tensile tests were carried on the compounds at different temperatures ranging from -20 to 90°C and crosshead speeds from 5 to 500 mm/min. The results were analyzed to determine how crosshead speed and temperature affected on the mechanical characteristics of CPVC specimens. Two damage models are then developed, one model obtained through by adapting the unified theory version and the other quasi-experimental static model based on ultimate stress. These models allow us to evaluate the damage evolution of CPVC samples and to determine the safety and maintenance intervals of this material.
Keywords: CPVC; Temperature; Crosshead speed; Damage; Unified theory